ANALISIS KESEHATAN BUMDES BERDASARKAN ASPEK PERMODALAN, LIKUIDITAS, KEMANDIRIAN DAN PERTUMBUHAN (Studi Kasus BUMDes Dana Asri Sejahtera Desa Wonoasri Kecamatan Tempurejo Kabupaten Jember) - Sari, Maheni Ika; Winahyu, Pawestri; Aini, Terawati Isro’ (Growth, 2022)
This study aims to determine and analyze the health of BUMDes based on aspects of capital, liquidity, independence and growth (case study of BUMDes Dana Asri Sejahtera, Wonoasri Village, Tempurejo District, Jember Regency). The analytical tool used in this study is an analysis of aspects of capital, liquidity, independence and growth. Based on the analysis results show that the health of BUMDes based on aspects of capital, liquidity, and growth is quite healthy. The factors that affect the health level of BUMDes Dana Asri Sejahtera in 2019-2020 are the estimated capital of BUMDes Dana Asri Sejahtera in meeting their operational needs. The ability of Dana Asri Sejahtera BUMDes to fulfill their short-term obligations, and the ability of Dana Asri Sejahtera BUMDes to produce SHU for capital or independence and or for institutional development, member dividends and operating expenses or expenses.